Habitat Characteristics and Diet of Bear Cuscus (Ailurops ursinus) in Tanjung Peropa Wildlife Reserve, Southeast Sulawesi - Rahmia , Rahmia Nugraha; Mustari, Abdul Haris Mustari (Forestry Department, University of Muhammadiyah Makassar, 2017)
Bear cuscus (Ailurops ursinus) which is vulnerable in the IUCN Redlist, is one of the endemic protected animal that lives in the lowland forests of Sulawesi. This research aimed to identify habitat characteristics, diet, and daily activities of bear cuscus in Tanjung Peropa Wildlife Reserve, Southeast Sulawesi. This research was carried out from February to March 2017. Habitat characteristics were identified using vegetation analysis, diet were identified using direct and non-direct observation, and daily activities were identified using ad-libitum sampling. The highest important value index of tree at the Mobula path and Mata Air path were Pisonia umbellifera (28.33 %) and Chisocheton ceramicus (44.72 %), respectively. The vegetation species diversity was high and the vegetation species evenness was distributed. A total of 80 species of plants were recorded which are the potential diet of bear cuscus. The highest percentage parts of plants that bear cuscus consumed were shoot (36.19 %) and young leaves (36.19 %). Bear cuscus daily activities were resting (89.05 %), moving (5.83 %), foraging (2.71 %), and feeding (2.41%). Bear cuscus preferred the C stratum of vegetation for their daily activities.